Avaliação do extrato aquoso dos frutos de Morinda citrifolia linn. (noni) nas alterações metabólicas em camundongos swiss alimentados com dieta rica em lipídios e frutose - Inada, Aline Carla (2021)
Metabolic syndrome (MS) encompasses a set of metabolic abnormalities. Studies have shown that Morinda citrifolia Linn. (noni) (M. citrifolia) has anticancer, antimicrobial, antiulcerogenic, antioxidative actions and actions on metabolic disorders involved in MS. Dysregulation in hepatic de novo lipogenesis (DNL) is one of metabolic disorders associated with MS and has a direct relationship with NAFLD. The aim of this study was to evaluate the oral action of two doses of a crude aqueous extract (AE) from fruits of M. citrifolia (AE) on biochemical and histopathological parameters and on the expression of genes involved in lipid and glycemic metabolism in animals fed a high-fat/high-fructose diet. AE was analyzed by ultra-fast liquid chromatography–diode array detector–tandem mass spectrometry (UFLC-DAD-MS). Acute oral toxicity was performed in female Swiss mice (n=10) divided in control group (CT) (n=5) and extract group (n=5) 2000 mg/kg according to OECD Guidelines 425 and the Hippocratic test was accomplished to evaluate morphological and behavioral feature from animals. To evaluate the extract treatment, 12-week-old male adult Swiss mice were submitted to a standard diet - control group (CT) (n=11) and a high-fat/high-fructose diet (HFF) (n=31) for 9 weeks. From the 10th week, treatment with extracts was started and the groups were divided into animals that were submitted to standard diet + drink water (CTW) (n=11), HFF diet + drink water (HFFW) (n=10), HFF diet + AE 250 mg/kg (HFF + AE 250) (n=11) and HFF diet + AE 500 mg/kg (HFF + AE 500) (n=10) daily until the 16th week. Animals were submitted for 8 hours of fasting to accomplish oral glucose tolerance test (OGTT) and was performed three days prior to the treatment and three days prior to euthanasia. Food intake, body mass, biochemical series, dosage of plasma insulin levels and histological analyzes of the liver, epididymal adipose tissue and pancreas were performed to determine biochemical and histological parameters. Quantitative real time - polymerase chain reaction (qRT-PCR) was used to evaluate the expression of some genes as peroxisome proliferator-activated receptors-α and -γ (PPAR-α and PPAR-γ), fatty acid enzymes synthase (FAS) and glucose-6-phosphatase (G6P), sterol regulatory element binding protein 1c (SREBP-1c), carbohydrate responsive element binding protein (ChREBP) and the hepatokine, fetuin-A. Seventeen compounds were tentatively identified including iridoids, noniosides and rutin. Animals that received the AE did not display signs and symptoms of acute toxicity. AE 500 mg/kg/day oral treatment improved glucose tolerance induced by HFF diet, however, both doses showed no effects on other biochemical and histological parameters. AE 500 mg/kg downregulated PPAR-α, SREBP-1c and fetuin-A mRNA expression in liver and upregulated PPAR-α mRNA expression in white adipose tissue, suggesting that the hypoglycemic action could be associated with the expression of genes involved in fructose metabolism and hepatic DNL.